2017
DOI: 10.1016/j.fsigen.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic approach for haplotype analysis of sequence data from complex mitochondrial mixtures

Abstract: Massively parallel (next-generation) sequencing provides a powerful method to analyze DNA from many different sources, including degraded and trace samples. A common challenge, however, is that many forensic samples are often known or suspected mixtures of DNA from multiple individuals. Haploid lineage markers, such as mitochondrial (mt) DNA, are useful for analysis of mixtures because, unlike nuclear genetic markers, each individual contributes a single sequence to the mixture. Deconvolution of these mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 53 publications
1
53
0
3
Order By: Relevance
“…This is particularly true when variants are present within a single amplicon or sequence read. Previous studies have demonstrated the utility of NGS for these purposes [44][45][46][47], and though further in depth studies that fully characterize the limitations of the PowerSeq assay for this application are necessary, the results presented here offer additional support.…”
Section: Discussionsupporting
confidence: 51%
“…This is particularly true when variants are present within a single amplicon or sequence read. Previous studies have demonstrated the utility of NGS for these purposes [44][45][46][47], and though further in depth studies that fully characterize the limitations of the PowerSeq assay for this application are necessary, the results presented here offer additional support.…”
Section: Discussionsupporting
confidence: 51%
“…In addition to GeneMarker ® HTS, the sequenced reads for the mtDNA mixture samples were analyzed using Mixemt developed by Vohr et al [ 54 ]. Prior to analysis using Mixemt, the raw sequence reads were trimmed for adapters, and the overlapping reads were merged using SeqPrep [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…54 However, these methods still have limitations because they are not able to identify the presence of contaminant DNA in the aDNA samples, which represents an actual hurdle in the analysis of ancient genomes. 14,15 To detect the contaminant DNA in the mixed aDNA samples, the mitochondrial DNA (mtDNA) can be used, as it is inherited only from the mother and it does not undergo recombination during meiosis (thus, each individual will be associated to a single haplotype) 55 and as each cell contains hundreds or thousands of it in identical copies. 55,56 In addition, detailed mtDNA databases, such as EMPOP 57 and MITOMAP, 58 can be used as reference databases for the identification of contaminant "modern" DNA in aDNA genomes.…”
Section: Mitochondrial Contaminations Of the Ancient Dnamentioning
confidence: 99%
“…14,15 To detect the contaminant DNA in the mixed aDNA samples, the mitochondrial DNA (mtDNA) can be used, as it is inherited only from the mother and it does not undergo recombination during meiosis (thus, each individual will be associated to a single haplotype) 55 and as each cell contains hundreds or thousands of it in identical copies. 55,56 In addition, detailed mtDNA databases, such as EMPOP 57 and MITOMAP, 58 can be used as reference databases for the identification of contaminant "modern" DNA in aDNA genomes. 55,[59][60][61] An iterative approach that can be used to identify the contaminant DNA in aDNA genomes is represented by the program Schmutzi.…”
Section: Mitochondrial Contaminations Of the Ancient Dnamentioning
confidence: 99%
See 1 more Smart Citation